Relation between executive function and academic achievement among children diagnosed with attention deficit and hyperactivity disorder - Hamza, Aya; El Latif Ghobashy, Soha; Abou El Wafa, Heba (Egyptian Journal of Psychiatry, 2021)
Background In spite of decades of progress in understanding attention-deficit hyperactivity disorder (ADHD) as a disorder of executive functions (EFs), there have been no significant number of studies exploring this executive dysfunction's effects on a child's daily life, more specifically the academic achievement domain, and it was long hypothesized that EFs affect child school performance and learning ability. Therefore, the identification of early, modifiable predictors of achievement can help guide efforts to improve the long-term success of many children and adolescents and to develop individualized educational strategies aimed at assisting children who struggle academically. Patients and methods This study examined different EF domains in a sample (N=100) of drug-naïve children aged 6-13 and having ADHD using the Barkley Deficits In Executive Functioning Scale-Children and Adolescents (BDEFS-CA). Moreover, all children were subjected to structured psychiatric interview as well as intelligence quotient testing and Conners' parent rating scale. Relations between complex EF and academic achievement were examined. Results Academic performance was highly correlated with intelligence quotient, whereas there is no significant difference between different subtypes of ADHD and EFs. The correlation between Conners' scale score signifying ADHD symptoms severity and academic achievement was insignificant. Finally, self-motivation EFs showed the highest significant correlation, suggesting a domain-general relation between complex EF and academic achievement. Conclusion Self-motivation is the main EF correlated with academic achievement in children with ADHD, and developing individualized educational programs for those children will improve scholastic achievement.